Architecture and Field Evaluation of an IoT-Integrated Village Information System for Public Service - Susilo Hartono; Tole Sutikno; Anton Yudhana (Telematika, 2026)
Village public services often struggle with slow administrative workflows, limited transparency, and unequal access to service information, particularly where processes remain manual and difficult to monitor in real time. This study evaluates a deployed integrated village information system augmented with Internet of Things (IoT) signals—RFID-based operational monitoring and water/electricity facility-status sensing—to assess whether service quality improved after implementation and to clarify the system mechanisms that plausibly explain observed changes. An explanatory sequential mixed-method design was applied. Quantitatively, a paired two-wave pre–post survey was completed by 100 residents (1 = strongly disagree, 5 = strongly agree) to measure Speed/Responsiveness, Accuracy (Information Quality), Ease of Access/Use, and Satisfaction. Qualitatively, in-depth interviews with village staff and residents, supported by field observations, were conducted to interpret quantitative shifts and identify constraints. Paired-sample tests indicated significant increases across all dimensions (p < 0.001) with medium-to-large effects (Cohen’s d_z = 0.58–0.92): Speed/Responsiveness increased from 3.12 to 3.76, Accuracy from 3.30 to 4.05, Ease of Access/Use from 3.15 to 3.70, and Satisfaction from 3.18 to 4.16. The qualitative strand linked these improvements to system-level features, including workflow digitalization with earlier verification and routing, administrative data validation with audit logging and digital archiving, and transparent request-status tracking via dashboards, while highlighting persistent risks related to connectivity reliability, operator capacity, digital inclusion for older residents, and personal-data governance. The contribution of this work is a systems-aware, field-based evaluation that couples an explicit IoT–information-system integration view (architecture, modules, and data lifecycle) with a two-wave paired outcome assessment and stakeholder explanations in a real village governance setting.